VARIATION OF MAXILLARY FIRST PREMOLAR WITH THREE ROOT CANALS - Janet Kirilova; Snezhanka Topalova-Pirinska; Dimiter Kirov (Peytchinski Publishing, 2014)
Background: Successful endodontic treatment requires effective biomechanical preparation of the root canals and three-dimensional obturation of the root canal system. This can be achieved only by knowing and identifying the variations in the root canal system of the endodontically treated teeth. The Aim: The aim of this article is to present cases of endodontic treatment of maxillary first premolar with three root canals - different types. Material and Methods: Five clinical cases of successful endodontic treatment of patients with maxillary first premolar and three root canals are described. Result and Discussion: It is noted that good endodontic practice requires good knowledge of dental anatomy and possible variations, accurate X-ray images, as well as use of magnifying equipment. Conclusion: Knowledge of dental anatomy is fundamental for good endodontic practice.